Best Practice: A Video Mediated Teaching of Phonology - Drs. Musta’in, M.Pd.; Wildan Isna Asyhar, M.Pd. (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2021)
A narrative inquiry as the approach of qualitative research is conducted in this research to know how the implementation of a video as a teaching media of Phonology and what the problems that the students face in using a video as the learning media of Phonology. This research involves 28 students of the second grade. The subject of research is the students of an English department in Education of UNISKA Kediri. The result is that there are four categorized problems that students face. Students felt that; (1) a native speaker in the video speaks too fast; (2) the pronunciation is unclear; (3) there are some new words or terms; (4) it is difficult to imitate the intonation and stressing of a word and sentence. However, the students can solve problems. Besides that, they get some advantages their ability in some aspects and are aware of the current issue; (1) the first is that the video is easy accessible; (2) the second one is that the video also is appropriate with the current issue so the students, beside learn about phonology, also aware of the current issue; (3) the other one is the students can learn and practice whenever with (out) the guidance of the lecturer; (4) the last advantage that we can offer is the students can listen the native speaker easily because they can play back the video when they cannot catch the word or meaning.